Associated Symptoms in the Ten Days Before Diagnosis of Kawasaki Disease - Baker, Annette L.; Lu, Minmin; Minich, L. LuAnn; Atz, Andrew M.; Klein, Gloria L.; Korsin, Rosalind; Lambert, Linda; Li, Jennifer S.; Mason, Wilbert; Radojewski, Elizabeth; Vetter, Victoria L.; Newburger, Jane W. (The Journal of pediatrics, 2009)
To describe common associated symptoms within the 10 days before diagnosis in subjects enrolled in the Pediatric Heart Network's trial of steroid therapy in Kawasaki disease (KD). Patients with acute KD were enrolled between days 4 and 10 of illness at 8 centers between 2002 and 2004. We defined common associated symptoms as those occurring in ≥10% of patients. Principal clinical criteria for KD were not included in this analysis. Among 198 patients, irritability was reported in 98 (50%), vomiting in 88 (44%), decreased food/fluid intake in 73 (37%), cough in 55 (28%), diarrhea in 52 (26%), rhinorrhea in 37 (19%), weakness in 37 (19%), abdominal pain in 35 (18%), and joint pain (arthralgia or arthritis) in 29 (15%). One or more gastrointestinal symptom (vomiting, diarrhea, or abdominal pain) was present in 120 patients (61%) and 69 patients (35%) had ≥ 1 respiratory symptom (rhinorrhea or cough). Nonspecific symptoms occur commonly in children with KD. To reduce delays in diagnosis, clinicians should be educated that such symptoms may comprise a significant component in the chief complaint.